A succinct review on the therapeutic potential and delivery systems of Eugenol - Muhammad Eleleemy; Basma Hamdy Amin; Maha Nasr; Omaima A. Sammour (Ain Shams University, 2020)
Eugenol; a botanical bioactive substance in clove, basil, cinnamon, and nutmeg was reported to exhibit several therapeutic benefits. Eugenia caryophyllata (i.e; clove) is the major natural source of eugenol with about forty-five to ninety percent of its essential oil. WHO recommended eugenol as a safe, non-mutagenic drug; therefore, it has attracted the attention of many scientists. Two main aspects are dealt with in the current review article, the pharmacological potential of eugenol and the innovative novel delivery systems used for enhancing the therapeutic efficacy of eugenol. In the former section, we summarized the therapeutic mechanisms/indications of eugenol, and in the latter section, we reported some nanotechnology-based carriers for the delivery of eugenol. Eugenol exhibits several pharmacological activities as an antioxidant, anti-inflammatory, antibacterial, antifungal, analgesic, anticancer, neuroprotective, antidiabetic, gastroprotective, and antihyperlipidemic. Several studies discussed combining eugenol with natural and synthetic drugs for enhancing their therapeutic effect with minimal side effects. The promising therapeutic activities of eugenol have led to the fabrication of novel eugenol-entrapped nano delivery systems as microemulsions, nanoemulsions, nanocapsules, solid lipid nanoparticles, liposomes, and ethosomes for further augmentation of its therapeutic activities as well exerting a sustained action. In conclusion, this concise review with some selected studies further complements the reports in the literature, stating that eugenol is a valuable compound in terms of its biological activities and that these biological activities can be enhanced by encapsulation in nanocarriers.